2020
DOI: 10.1111/jdv.16498
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in TRPV3 causes painful focal plantar keratoderma

Abstract: Mutation in TRPV3 causes painful focal plantar keratoderma Editor Hereditary palmoplantar keratoderma (PPK) belongs to a group of genetically and clinically heterogeneous genodermatoses characterized by diffuse, focal, striate or punctate hyperkeratosis of the sole and palm skin. A painful form of PPK was recently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Gain-of-function mutations in TRPV3 were discovered in patients with Olmstedt disease 103 , 104 , erythromelalgia 104 , and painful plantar keratoderma 105 . As with TRPA1 above, many of these TRPV3 gain-of-function mutations are at the elbow connecting the S4−S5 linker and the S5 helix (Fig.…”
Section: Pain: Trp Channels As Analgesic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gain-of-function mutations in TRPV3 were discovered in patients with Olmstedt disease 103 , 104 , erythromelalgia 104 , and painful plantar keratoderma 105 . As with TRPA1 above, many of these TRPV3 gain-of-function mutations are at the elbow connecting the S4−S5 linker and the S5 helix (Fig.…”
Section: Pain: Trp Channels As Analgesic Targetsmentioning
confidence: 99%
“…In humans, gain-of-function TRPV3 mutations (G568D and Q580P; Fig. 3b ) were described in palmoplantar keratoderma 105 , and increased TRPV3 expression was reported in post-burn pruritus 217 . Similarly, TRPV4 is overexpressed in skin biopsy samples from patients with chronic pruritus 218 , and genetic deletion of Trpv4 ameliorates itching in mouse models of chronic itch 219 .…”
Section: Dermatology and Ophthalmologymentioning
confidence: 99%
“…Our results revealed that citrusinine-II could cross the blood-brain barrier and therefore citrusinine-II might be involved in the regulation of the descending pain pathway. These findings suggest that citrusinine-II is a valuable candidate drug for the treatment of pruritus-related diseases and that TRPV3 channel is a promising therapeutic target for treating severe itching and pain, as clinically reported in palmoplantar keratoderma and Olmsted syndrome (Choi et al, 2018;Peters et al, 2020).…”
Section: Discussionmentioning
confidence: 68%
“…Although there is no overwhelming evidence that TRPV3 has a definite role in analgesic therapy, some reports suggest that TRPV3 channel maybe pain-related (Carreno et al, 2012;Huang & Chung, 2013;Park et al, 2016). In addition, hereditary palmoplantar keratoderma, a rare genetic disorder which is partly due to TRPV3 gain-of-function mutation, is also characterized by severe pain and debilitating itch (Peters et al, 2020). Therefore, we tested the analgesic activity of citrusinine-II on several rodent pain models in which pain was induced by formalin, acetic acid or heat.…”
Section: Citrusinine-ii Alleviates Pain Behaviour In Rodent Modelsmentioning
confidence: 99%
“…As a member of TRPV subfamily similar to TRPV1, TRPV3 is suspected to have similar nociceptive sensation function to TRPV1, although this view is still controversial [ 15 , 18 , 44 ]. Most studies have supported the function of TRPV3 in nociceptive sensation.…”
Section: Physiological and Pathological Functions Of Keratinocytes-ex...mentioning
confidence: 99%